El Banco de la Nación y su rol facilitador en la inclusión financiera - Soto Rodríguez, Jimmy Henry (2021)
Financial Inclusion is the access (points of attention and infrastructure) and use (frequency and intensity of employment) of quality financial services and products (financial services that satisfy needs) by all segments of the population, in the Banco de The Nation's Mission is: "To provide quality services to citizens and the State, expanding our coverage of services and promoting financial inclusion, through modern and self-sustainable management" (Banco de la Nacion [BN], 2020). The main objective of this work is to determine the role that Banco de la Nacion has played as a facilitator in Financial Inclusion in the country, and for this purpose, the progress made by the Bank in the dimensions of use, access and quality was analyzed. For this, an analysis of the indicators that the Bank contemplates for the strengthening of financial inclusion until 2018 was carried out, in addition to describing the actions developed during my work and professional performance in the operations area, indirectly contributing to the dimension of access and quality, and directly in the dimension of use because they actively participated in financial education operations, participating with mobile banking in vulnerable areas, and training micro finance companies in granting loans. Achieving a 40% increase in customer service, a 50% decrease in the receipt of complaints and claims.